Analyzing the Impact of Social Media Advertising on Consumer Interactions, Trust, and Purchase Intentions in the Cosmetics and Personal Care Sector - Yee, Loo Shu; Hoo, Wong Chee; Wolor, Christian Wiradendi; Bakar, Syarifah Mastura Syed Abu; Nurkhin, Ahmad (Journal of Applied Data Sciences, 2025)
This study analyses the influence of social media advertisements on consumer purchasing intentions within Malaysia's cosmetics and personal care sector, highlighting the significance of interactivity, informativeness, and trust. Considering the growing prevalence of social media in marketing, comprehending how these elements affect consumer choices is crucial for enhancing digital advertising strategies.  This research utilises a quantitative approach to evaluate consumer behaviour. Data were gathered from 384 Malaysian consumers aged 18 and older who actively interact with cosmetic and personal care brands on social media using online survey. The research employed descriptive analysis, reliability and validity assessments, and hypothesis testing to investigate the relationships among principal variables.  Research demonstrates that informativeness and trust in social media advertisements substantially increase purchase intentions, with trust acting as a vital mediator. Although interactivity enhances trust, it does not directly affect purchase intention, indicating that its influence may be contingent upon contextual variables. These findings underscore the imperative for brands to deliver transparent, reliable, and informative content to enhance consumer trust and stimulate purchasing behaviour. The study's originality is rooted in its examination of the Malaysian cosmetics and personal care market, providing practical insights for marketers to enhance social media advertising strategies. The research underscores trust as a pivotal factor, offering essential insights for brands aiming to improve their digital engagement. This study enhances the existing literature on digital marketing in emerging markets, providing practical insights for businesses seeking to improve their social media efficacy in Malaysia.